DIGNAR-19 Toolkit Manual - Aligishiev, Zamid (Technical Notes and Manuals; Technical Notes and Manuals ;, 2021)
This note is a user's manual for the DIGNAR-19 toolkit, an application aimed at facilitating the use of the DIGNAR-19 model by economists with no to little knowledge of Matlab and Dynare via a user-friendly Excel-based interface. he toolkit comprises three tools-the simulation tool, the graphing tool, and the realism tool-that translate the contents of an Excel input file into instructions for Matlab/Dynare programs. These programs are executed behind the scenes. Outputs are saved in a separate Excel file and can also be visualized in customizable charts.